Stomach Content Analisys Of Stripped Flying Barb (Esomus Metallicus) In The Riau University Waters - Sukron, M.; Putra, Ridwan Manda; ', Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Stripped flying barb fish (Esomus metallicus) is common in the waters around the Riau University. A study aims to determine the stomach content of the fish was conducted in May 2017. There were three sampling areas, the earthen pool around the Rektorat Building (Station 1), dam (Station 2), and a stream in the back of Marine Science Building (Station 3). Sampling was done three times,  once/week. The fish was captured using a scoop net. Total number of fish sampled was 40. Results shown that the main food of the fish is phytoplankton (IP>40%), the complementary food is detritus (IP 4-40%), and additional food is zooplankton and crustacean remains (IP<4%).Key Word: E. Metallicus, University of Riau, Pool, Dam, Stream